Annual variation in sensory characteristics of seventeen apple cultivars - Seppä, Laila; Tahvonen, Risto; Tuorila, Hely (Agricultural and Food Science, 2016)
Sensory characteristics of 17 apple cultivars commonly grown in Finland were compared over three harvest years (2009–2011). Descriptive analysis with a trained panel (n = 11–14) comprised 17 attributes rated from 0 (‘not at all’) to 10 (‘very’): four appearance (green, red, area of red colour, skin waxiness), three odour (intense, grassy, fruity), five texture (hard, crispy, mealy, juicy, tough peel), and five flavour (intense, sour, sweet, astringent, diverse) attributes. Ratedintensities differed between the harvest years but their magnitude and direction of change varied according to the cultivar. Odour and flavour ratings tended to be higher in 2009 than in 2010 and 2011. The summer 2009 was fairly normal, while summer 2010 was hot and dry, and summer 2011 hot and humid. These climate may explain some of the differences between the first and the two subsequent years. Late season cultivars tended to be relatively stable against annual effects.